Optimization of fermentation media for citric acid production using empty fruit bunches as substrate by central composite design - Alam, Md. Zahangir; Jamal, Parveen; Basri, S Maryam H (2007)
A solid state fermentation method will be carried out for the production of citric acid from empty fruit bunches (EFB) by employing the potential fungus Aspergillus niger (A106). Statistical optimization was carried out in terms of media composition and fermentation time by central composite design (CCD) to evaluate the polynomial regression model through effects of linear, quadratic and interaction of the factors. The factors involved were co-substrates concentration (glucose and wheat flour),nutrient concentration and fermentation day. The result from regression model and statistical analysis showed that glucose was the significant factor that contributed to the highest citric acid production. The maximum citric acid (3.9 g/l) was observed with the optimum fermentation conditions of 3% of glucose, 1% of wheat flour and 6% nutrient concentration, and 7 days of fermentation period.